Agglomeration Dynamics of 1D Materials: Gas‐Phase Collision Rates of Nanotubes and Nanorods. Issue 27 (23rd May 2019) - Boies, Adam M.; Hoecker, Christian; Bhalerao, Ajinkya; Kateris, Nikolaos; de La Verpilliere, Jean; Graves, Brian; Smail, Fiona
Abstract: The agglomeration and self‐assembly of gas‐phase 1D materials in anthropogenic and natural systems dictate their resulting nanoscale morphology, multiscale hierarchy, and ultimate macroscale properties. Brownian motion induces collisions, upon which 1D materials often restructure to form bundles and can lead to aerogels. Herein, the first results of collision rates for 1D nanomaterials undergoing thermal transport are presented. The Langevin dynamic simulations of nanotube rotation and translation demonstrate that the collision kernels for rigid nanotubes or nanorods are ≈10 times greater than spherical systems. Resulting reduced order equations allow straightforward calculation of the physical parameters to determine the collision kernel for straight and curved 1D materials from 10 2 to 10 6 nm length. The collision kernels of curved 1D structures increase ≈1.3 times for long (>10 2 nm), and ≈5 times for short (≈10 2 nm) relative to rigid materials. Applications of collision frequencies allow the first kinetic analysis of aerogel self‐assembly from gas‐phase carbon nanotubes (CNTs). The timescales for CNT collision and bundle formation (0.3–42 s) agree with empirical residence times in CNT reactors (3–15 s). These results provide insights into the CNT length, number, and timescales required for aerogel formation, which bolsters our understanding of mass‐produced 1D aerogel materials. Abstract : The agglomeration of gas‐phase 1D materials (nanotubes, nanorods, or fibers) is a result of Brownian‐induced collisions. Herein, the collision rates for 1D nanomaterials are presented and it is demonstrated that the collision kernels for nanotubes are ≈10 times greater than spherical systems. Applications of collision frequencies show that the timescales for carbon nanotube collision and bundle formation agree with reactor residence times.